Synergy Collaboration Management as A Catalyst for the Performance of Catholic Religious Education Teachers in Central Kalimatan - Fransiskus Janu Hamu; Emiliana Sri Pudjiarti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the effect of transformational leadership on the performance of PAK (Christian Religious Education) teachers mediated by individual spiritual involvement, collaboration synergy and professional altruistic behavior as mediating variables. This type of research is survey research. The population in this study were PAK teachers in Central Kalimantan, while the sample in this study were 173 PAK teachers in Central Kalimantan. The instrument used to answer the research questions posed, the sampling technique was stratified random sampling. This study used primary data sources, questionnaires and the data analysis technique used is the Structural equation model with SmartPLS. The results of this study indicated that transformational leadership has a positive impact on PAK teacher performance by mediating PAK teacher spiritual involvement, collaborative synergy and professional altruistic behavior.  Related to the involvement of spirituality, then a teacher will have meaning and value in life and work as a PAK teacher, where these meanings and values are highly dependent on the beliefs and values that underlie the motives in work which in turn encourages the birth of altruistic professional behavior that causes positive feelings.